Trace metals in aquatic systems - Mason, Robert P. (Robert Peter), 1956- (John Wiley & Sons, 2013)
"The textbooks that currently exist do not deal with this particular subject in a comprehensive fashion, and therefore this book is being proposed to full this gap"--